A molecular dynamics study of the nucleus interface structure and orientation relationships during the austenite-to-ferrite transformation in pure Fe. (2nd January 2018) - Song, H.; Hoyt, J. J.
ABSTRACT: Molecular dynamics simulations using an embedded-atom method potential for pure iron (Fe) were performed to investigate the solid-state transformation of a body-centred-cubic phase from a polycrystalline face-centred-cubic matrix. A Kurdjumov–Sachs orientation relationship accompanied with a step-ledge disconnection structure was detected in high mobility phase boundaries of a full 3D classical and barrier-free nucleation specimen. The results imply that interface coherency is an important factor for both nucleation and growth processes, which may significantly affect the transition rate of the austenite–ferrite transformation.